Phosphomannosylation and the Functional Analysis of the Extended Candida albicans MNN4-Like Gene Family - González-Hernández, Roberto J.; Jin, Kai; Hernández-Chávez, Marco J.; Díaz-Jiménez, Diana F.; Trujillo-Esquivel, Elías; Clavijo-Giraldo, Diana M.; Tamez-Castrellón, Alma K.; Franco, Bernardo; Gow, Neil A. R.; Mora-Montes, Héctor M. (Frontiers in Microbiology, 2017)
Phosphomannosylation is a modification of cell wall proteins that occurs in some species of yeast-like organisms, including the human pathogen Candida albicans. These modified mannans confer a negative charge to the wall, which is important for the interactions with phagocytic cells of the immune systems and cationic antimicrobial peptides. In Saccharomyces cerevisiae, the synthesis of phosphomannan relies on two enzymes, the phosphomannosyltransferase Ktr6 and its positive regulator Mnn4. However, in C. albicans, at least three phosphomannosyltransferases, Mnn4, Mnt3 and Mnt5, participate in the addition of phosphomannan. In addition to MNN4, C. albicans has a MNN4-like gene family composed of seven other homologous members that have no known function. Here, using the classical mini-Ura-blaster approach and the new gene knockout CRISPR-Cas9 system for gene disruption, we generated mutants lacking single and multiple genes of the MNN4 family; and demonstrate that, although Mnn4 has a major impact on the phosphomannan content, MNN42 was also required for full protein phosphomannosylation. The reintroduction of MNN41, MNN42, MNN46 or MNN47 in a genetic background lacking MNN4 partially restored the phenotype associated with the mnn4Δ null mutant, suggesting that there is partial redundancy of function between some family members and that the dominant effect of MNN4 over other genes could be due to its relative abundance within the cell. We observed that additional copies of alleles number of any of the other family members, with the exception of MNN46, restored the phosphomannan content in cells lacking both MNT3 and MNT5. We, therefore, suggest that phosphomannosylation is achieved by three groups of proteins: [i] enzymes solely activated by Mnn4, [ii] enzymes activated by the dual action of Mnn4 and any of the products of other MNN4-like genes, with exception of MNN46, and [iii] activation of Mnt3 and Mnt5 by Mnn4 and Mnn46. Therefore, although the MNN4-like genes have the potential to functionally redundant with Mnn4 they apparently do not play a major role in cell wall mannosylation under most in vitro growth conditions. In addition, our phenotypic analyses indicate that several members of this gene family influence the ability of macrophages to phagocytose C. albicans cells.